The football championship is won when playing away: difference in match statistics between the winner and the second-place team in LaLiga - Del Coso, J.; Brito de Souza, D.; Lopez-Del Campo, R.; Blanco-Pita, H.; Resta, R. (International Journal of Performance Analysis in Sport, 2020)
The aim of this study was to identify match statistics that best explained the differences between the first- and the second-placed teams in the Spanish National football championship (LaLiga). For this aim, the number of wins, draws, losses, distribution of scored/received goals, and accumulated attack, and defensive match statistics were obtained of the 1st and 2nd place teams for eight seasons (from 2010-2011 to 2017-2018). In comparison to the championship winner, the second-place team obtained a similar number of victories at home but a lower number of away wins (effect size [ES] = moderate). The goal-based variables with the highest effect size between the first- and second-place teams were a higher number of goals scored while playing away and a lower number of goals received while playing away (ES = moderate). A higher shooting accuracy along with less conceded shots and conceded corners (ES = moderate), were the match statistics with the highest effect size between the investigated teams. A higher number of wins when playing away was the best indicator of performance to differentiate between the championship winner and the second-place team. Increased shooting accuracy and conceding less shots from corners might also aid in obtaining victory in LaLiga.